2021
DOI: 10.1093/jbi/wbab086
|View full text |Cite
|
Sign up to set email alerts
|

Online or Offline: Does It Matter? A Review of Existing Interpretation Approaches and Their Effect on Screening Mammography Metrics, Patient Satisfaction, and Cost

Abstract: The ideal practice routine for screening mammography would optimize performance metrics and minimize costs, while also maximizing patient satisfaction. The main approaches to screening mammography interpretation include batch offline, non-batch offline, interrupted online, and uninterrupted online reading, each of which has its own advantages and drawbacks. This article reviews the current literature on approaches to screening mammography interpretation, potential effects of newer technologies, and promising a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…While mammographic screening finds the majority of malignancies with relatively few false-positive findings, there is still considerable room for improvement, including in the reading process. Multiple studies have shown that batch reading improves screening performance, specifically a reduction in radiologists’ false-positive rates, compared to “interrupted” reading that includes other clinical duties (Burnside et al, 2005; Cohen et al, 2021; Ram et al, 2022). This improvement is robust to changes in the technology used to acquire images (screen-film, digital, and digital breast tomosynthesis mammography systems), indicating that the source of these effects lies within the reader.…”
Section: Adaptation To Specialized Environments – the Case Of Medical...mentioning
confidence: 99%
“…While mammographic screening finds the majority of malignancies with relatively few false-positive findings, there is still considerable room for improvement, including in the reading process. Multiple studies have shown that batch reading improves screening performance, specifically a reduction in radiologists’ false-positive rates, compared to “interrupted” reading that includes other clinical duties (Burnside et al, 2005; Cohen et al, 2021; Ram et al, 2022). This improvement is robust to changes in the technology used to acquire images (screen-film, digital, and digital breast tomosynthesis mammography systems), indicating that the source of these effects lies within the reader.…”
Section: Adaptation To Specialized Environments – the Case Of Medical...mentioning
confidence: 99%
“…Batch reading is now common practice for evaluating breast-cancer screening images, with evidence from a variety of clinical studies suggesting that it improves screening performance [1][2][3][4] , even when implemented in an immediate-read 5,6 setting (for a review, see Ram et al 7 ). This has spurred interest in identifying the mechanisms of this improved performance, and characterizing sequential effects within a batch of cases [8][9][10] .…”
Section: Introductionmentioning
confidence: 99%